2007
DOI: 10.5194/npg-14-587-2007
|View full text |Cite
|
Sign up to set email alerts
|

Energetic particle parallel diffusion in a cascading wave turbulence in the foreshock region

Abstract: Abstract.We study parallel (field-aligned) diffusion of energetic particles in the upstream of the bow shock with test particle simulations. We assume parallel shock geometry of the bow shock, and that MHD wave turbulence convected by the solar wind toward the shock is purely transverse in one-dimensional system with a constant background magnetic field. We use three turbulence models: a homogeneous turbulence, a regular cascade from a large scale to smaller scales, and an inverse cascade from a small scale to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The upstream-propagating waves excited by the beam instability of energetic ions reaching far upstream (up to 1750 R E in the radial direction according to Desai et al [2008]) can undergo an inverse cascade to generate UPAFs [Giacalone, 2004;Otsuka et al, 2007]. These energetic ions keep propagating upstream, while the UPAFs are transported downstream by the solar wind and thus are separated from the source ions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upstream-propagating waves excited by the beam instability of energetic ions reaching far upstream (up to 1750 R E in the radial direction according to Desai et al [2008]) can undergo an inverse cascade to generate UPAFs [Giacalone, 2004;Otsuka et al, 2007]. These energetic ions keep propagating upstream, while the UPAFs are transported downstream by the solar wind and thus are separated from the source ions.…”
Section: Discussionmentioning
confidence: 99%
“…Giacalone [2004] made a large-scale hybrid simulation at a parallel shock and found that near the shock, the spectrum of self-excited waves in the frequency range of 2 × 10 −3 to 0.1 Hz is approximately a power law with an index close to −5∕3. Otsuka et al [2007] proposed that if wave-wave interactions occur as the high-frequency waves are transported by the solar wind to the bow shock, the inverse cascade will take place. However, the previous observational studies all focused on monochromatic waves.…”
Section: Introductionmentioning
confidence: 99%